A Spectroscopic Methodology to Early Detection of Urinary Tract Infections - Ana F. N. S. Mendes; Nuno Matela; João M. P. Coelho; Joaquim T. Marquês (Sensors)
Healthcare-associated infections (HAI) are a critical public health problem, with 30 to 40% of infections related to the urinary tract system. These urinary tract infections (UTIs) are considered one of the most common microbial infections in hospital settings and everyday community contexts, where approximately 80% are highly correlated with urinary catheter insertion, i.e., catheter-associated urinary tract infections (CAUTIs). Considering that 15 to 25% of hospitalised patients need to be catheterised during their treatments and most CAUTIs are asymptomatic, it results in a tremendous challenge to provide an early diagnosis of CAUTI and therefore initiate its treatment. The lack of standardised methods as a first step for urine monitoring and early detection of UTIs is the driving force of this work, which aims to explore the potential of absorption and fluorescence spectroscopic methodologies to detect UTIs. Urine samples were used without any previous treatment to target the most straightforward testing protocol possible. In this work, we successfully developed a powerful methodology that combines ratiometric fluorescence spectroscopy measurements and transmittance at 600 nm to distinguish healthy urine from infected urine. The complementary use of fluorescence spectroscopy and transmittance is what makes the new methodology we propose such a powerful approach to monitor urine samples and provide early detection of UTIs since it provides a quantitative analysis of both healthy and infected urine.